2018
DOI: 10.1249/mss.0000000000001460
|View full text |Cite
|
Sign up to set email alerts
|

Sensor-enabled Activity Class Recognition in Preschoolers

Abstract: Machine learning algorithms such as RF and SVM are useful for predicting PA class from accelerometer data collected in preschool children. Although classifiers trained on hip or wrist data provided acceptable recognition accuracy, the combination of hip and wrist accelerometer delivered better performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 31 publications
2
49
0
Order By: Relevance
“…Over the last decade, there has been a shift from count-based thresholds to machine learning activity classification and energy expenditure estimation algorithms based on features extracted from raw accelerometer signals [15]. When applied to youth, machine learning approaches have shown to provide more accurate predictions of physical activity intensity [13,16]. Moreover, in contrast to cut-point methods, which only estimate time spend in MVPA, physical activity classification models can predict time spent in specific activity types (e.g., walking, running, dancing, cycling) or broader activity classes (e.g., active games or sports) [13,16].…”
Section: Stewart G Trostmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last decade, there has been a shift from count-based thresholds to machine learning activity classification and energy expenditure estimation algorithms based on features extracted from raw accelerometer signals [15]. When applied to youth, machine learning approaches have shown to provide more accurate predictions of physical activity intensity [13,16]. Moreover, in contrast to cut-point methods, which only estimate time spend in MVPA, physical activity classification models can predict time spent in specific activity types (e.g., walking, running, dancing, cycling) or broader activity classes (e.g., active games or sports) [13,16].…”
Section: Stewart G Trostmentioning
confidence: 99%
“…When applied to youth, machine learning approaches have shown to provide more accurate predictions of physical activity intensity [13,16]. Moreover, in contrast to cut-point methods, which only estimate time spend in MVPA, physical activity classification models can predict time spent in specific activity types (e.g., walking, running, dancing, cycling) or broader activity classes (e.g., active games or sports) [13,16]. This enables researchers in the public health and exercise sciences to explore a greater variety of physical activity metrics as well as examine age-related differences in movement behaviours that are not confounded by developmental differences in the relationship between accelerometer counts and energy expenditure.…”
Section: Stewart G Trostmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of accelerometry studies as well as in other fields of research can explain why the idea of merging data from multiple population groups and different wear locations is plausible. The use of multiple accelerometers (e.g., hip and wrist) has shown improvements in the prediction accuracy of classification models [40]. For instance, classifying energy-consuming activities in which the wrist motion is limited (e.g., cycling) has been shown to be challenging with wrist accelerometers while the presence of motion from other wear locations (e.g., hip) seems to help classify such activities more accurately (or vice versa for other activities) [15].…”
Section: B Merging Various Data Sources To Improve the Generalizatiomentioning
confidence: 99%
“…However, Koster et al [ 6 ] pointed out that wrist accelerometers underestimated the sedentary time and in some scenarios sitting time may not be distinguished from standing time-based on accelerometer data. A recent study by Trost et al [ 7 ] using ActiGraph accelerometer on the right hip and nondominant wrist showed 90% accuracy for recognition of sedentary behavior among preschoolers. Authors used Radom Forest and support vector machine classifiers.…”
Section: Introductionmentioning
confidence: 99%